2017
DOI: 10.1097/md.0000000000008241
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of oncological outcomes of right-sided colon cancer versus left-sided colon cancer after curative resection

Abstract: Propose:There are embryological origins, anatomical, histological, genetic, and immunological differences between right-sided colon cancer (RCC) and left-sided colon cancer (LCC). Many studies have sought to determine the survival and prognosis according to tumor location. This study aimed to analyze outcomes between RCC and LCC.Material and method:Between January 2000 and December 2012, data on 414 patients who underwent curative resection for RCC and LCC were retrieved from a retrospective database. Propensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
77
1
9

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(102 citation statements)
references
References 27 publications
12
77
1
9
Order By: Relevance
“…It was observed that patients with right-sided tumors presented a significantly decreased OS compared to left-sided tumors. This phenomenon has also been described previously [39][40][41][42]. Baran B et al reported that treatment response differed among the left and right-sided tumors.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…It was observed that patients with right-sided tumors presented a significantly decreased OS compared to left-sided tumors. This phenomenon has also been described previously [39][40][41][42]. Baran B et al reported that treatment response differed among the left and right-sided tumors.…”
Section: Discussionsupporting
confidence: 82%
“…Moreover, the higher antigenic load described in the right-sided tumors is more likely to be due to the defective mismatch repair mechanism because of the high frequency of mutations, thus increasing the possibility of immune recognition [46,47]. Lim DR et al described data from 414 patients under curative resection for right or left-sided colon cancer, suggesting that patients with left-sided tumors had a better survival outcome than those with right-sided tumors, especially in stage III patients [41]. Finally, Ulanja MB et al, in a retrospective analysis of 163,980 patients with colon cancer, concluded that tumor sidedness might affect presentation and survival rates at different stages of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Eklof et al also found that RCC with an increase in BRAF mutations exhibits poor prognosis. Moreover, RCC usually presents with advanced stage, increased tumor size, poorer differentiation, and more node positivity than LCRC, which are related to inferior survival …”
Section: Discussionmentioning
confidence: 99%
“…В ходе исследования обнару-жилось, что в источниках литературы не представлены в полном объеме данные по отдаленным результатам экстренной хирургии рака ОК. В большинстве проведенных исследований и сис-тематических обзоров было продемонстрировано, что показатели 5-летней выживаемости в плановой хирургии рака ОК были несколько лучше при левосто-ронней локализации опухоли по сравнению с право-сторонней [15][16][17][18][19][20]. Так, в исследовании K. Moritani и соавт.…”
Section: Discussionunclassified
“…Lim и соавт. [16], IIIС стадия наблю-далась чаще при правостороннем раке ОК по срав-нению с левосторонним, хотя различия не были ста-тистически значимыми. Кроме того, имеются данные о том, что правосторонний рак ОК имеет более низкую дифференцировку по сравнению с левосторонним, чаще встречается у пациентов более старшего возраста и при правых локализациях рака ОК чаще поражаются апикальные лимфатические узлы [16,21,24], что ока-зывает непосредственное влияние на прогноз заболе-вания.…”
Section: Discussionunclassified